Legal Protection of the Office of Notary against the Principle of Confidentiality in View of Article 66 Paragraph (4) of the Notary Law - Nadhea Tungga Devi; Ariawan Gunadi (Dinasti Research, 2024)
This article is entitled “Legal protection of notary positions against the principle of confidentiality in review of Article 66 paragraph (4) of the UUJN”. The research method used is normative juridical research, using secondary data to analyze legal issues. The result of the research is that the legal protection of notaries in maintaining the confidentiality of the contents of their authentic deeds is not effective with the application of article 66 paragraph (4) of the UUJN by law enforcement in examining notaries. This is due to the absence of implementing regulations for article 175 of Law No. 6 of 2023 Jo article 66 paragraph (4) of UUJN, which has implications for the examination of notaries without protection and legal defense efforts to submit to law enforcement photocopies of the Deed Minute and/or letters attached to the Deed Minute or Notary Protocol in the Notary's storage which are confidential and guaranteed by law. Direct examination of notaries based on Constitutional Court Decision 20 PK/PID/2020 if MKN does not respond to law enforcement's request for notary examination (Article 66 (4) UUJN).